Factors that affect the retention of - Gruber, Andrew (My University, 2011)
The intense competition for talented individuals has become a global phenomenon brought about by the social transformation of the knowledge age, leaving no organisation unaffected. The skills shortage experienced by knowledge-intense organisations, such as engineering consultancies, is constraining them from meeting their business objectives as they struggle to attract and retain talented individuals. Given this context, this research focuses on understanding retention factors that are important to consulting engineers in an engineering contracting company in South Africa. Semi-structured interviews were conducted with 17 engineers, three line managers and an HR practitioner in charge of retention in a multinational engineering company operating in South Africa to determine the important retention factors that affect engineers. The findings of the research suggest that engineers are retained by four distinct factors. Two of those are linked to their personal development (career growth and leaning opportunities), one is associated with the intrinsic rewards gained from completing work, and the last is the salary received. Additionally, a rankorder questionnaire was completed by the respondents to confirm the findings obtained in the interviews. The correlation between the two sets of results was high. The findings obtained from the HR representative and managers indicate that the people in charge of retention generally understood the factors that retained their engineering staff, but not fully. Although the findings from this research cannot be generalised to all engineering contracting organisations in South Africa, they do suggest that retaining consulting engineers is a complex phenomenon that management should pay heed to.
MBA - WBS
Keywords: Retention of staff; Engineers, retention of; Contractors